Efficient and Secure Authentication Scheme with Conditional Privacy‐Preserving for VANETs. Issue 5 (1st September 2016) - Xie, Yong; Wu, Libing; Zhang, Yubo; Shen, Jian
Abstract : The goal of authentication scheme for Vehicular ad hoc networks (VANETs) is to ensure reliability and integrity of message. Due to the timeliness of traffic‐related messages and the highly dynamic nature of VANETs, it still is a challenge to solve the three key issues simultaneously, i.e. security, efficiency and conditional privacy‐preserving, on the design of authentication scheme for VANETs. To address this challenge, an efficient Conditional privacy‐preserving authentication (CPPA) scheme is proposed in this paper. Compared with the most recent proposed CPPA schemes, our proposed scheme markedly decreases the computation costs of the message‐signing phase and the message verification phase, while satisfies all security requirements of VANETs and provides conditional privacy‐preserving.